PENERAPAN AKAD IJARAH PADA PRODUK RAHN DI CABANG PEGADAIAN SYARIAH ISTIQLAL MANADO - Rosdalina Bukido; Faradila Hasan (Jurnal Ilmiah Al-Syir'ah, 2016)
Product practices in Islamic Financial Institutions (LKS) have so far attracted specialattention, especially on the application of the contract. The fundamental differencesbetween the LKS and the conventional financial institutions are contracts/agreementsbefore making financial transactions. Many conducted research on the application ofthe LKS contracts. Some contracts madeby LKS on its products so farhave notcomplied withthesharia provisions. The basic rule refers to thefatwa (religiousadvisory opinions) of the National Sharia Board and the Council of IndonesianUlema (DSN-MUI). One of them is DSN-MUI fatwa No. 25 of 2002 concerningrahn. In addition to rahn, this fatwa also explains rules concerning the contract ofijara. Pawnshopsthat apply sharia principles in their products haveintroducedrahnproducts based on this the fatwa. Therefore, systematic research on the application ofthe ijara contract onrahn products is necessary.Keywords: ijara , rahn, DSN-MUI, sharia pawhshop.